Perception Of Art Education Students Class Of 2023 Faculty Of Art And Design Makassar State University On The Basic Selection Courses Of Theater - Andi Ananta Asbar; Djirong, Agussalim; Mukaddas, Andi Baetal (Journal of Arts Education and Design, 2025)
This Perception Of Art Education Students Class Of 2023 Faculty Of Art And Design Makassar State University On The Basic Selection Courses Of Theater The research employed a descriptive qualitative approach using a survey method. Data were collected through observation, interviews, and documentation involving all students who had taken the course. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that students generally have positive perceptions of the Basic Theatre course. These perceptions are influenced by internal factors, including interest, curiosity, and motivation for self-development, as well as external factors such as the lecturer’s teaching methods and a supportive learning environment. Despite initial challenges such as shyness and nervousness, the course contributes to increased self-confidence, communication skills, mastery of body and vocal expression, and shows strong relevance to visual art creation and the pedagogical readiness of students as future art educators.